Pengembangan Modul Pelatihan Pembuatan Gerabah Di Desa Masbagik Timur - ali, muhamad; Aprilianti, Ana (Universitas Hamzanwadi, 2019)
Research on development of training module of making pottery is very important to build new entrepreneur in increasing economic activity of society. This research and development aims to produce vessel training modules, training manuals and to explain the effectiveness of pottery-making training modules, training manuals to improve economic activities of communities in Masbagik Timur Village. Research and Development (R & D) research methods. Stages of product development, (a) preparation of training modules, (b) guide on making pottery, and (c) assessment. Data collection techniques used observation, interviews and questionnaires. Data analysis techniques, (a) validity, (b) readability, and (c) effectiveness. Module validation is done by experts and practitioners. The module trials include a limited trial of 6 communities and an expanded trial of 10 Masbagik Timur Village communities. The results showed; (1) validated products of experts and practitioners get a mean score of 2.0% (good qualification), (2) final module development training worthy of use. Average readability 3.7 (good qualification), there is practicality in using this training module with a mean of 3.6 (good qualification), effective module to use. The conclusion of the research is that the training module of pottery making and its training manual is feasible to be used to improve the economic activity of Masbagik Timur Masbagik Village community